(untitled) (Global Journal of Human-Social Science, 2018)
Terrorism, global terrorism, and global religious terrorism represent three different levels of the phenomenon. Despite the word «terrorism» being associated with a period of the French Revolution of 1789, terrorism is much older. However, global terrorism only dates back to almost 150 years, as it began with the anarchist wave (Rapoport, 2001) in the last decades of the 19th century, and global religious terrorism is the most recent wave as it started with the Islamic Revolution in Iran. In this evolution, the role of women in terrorism has changed over time, and when religion made its appearance in the phenomenon, it reached a crucial position, even in the communities where women are not regarded as man’s equals. This paper provides a snapshot of global female jihadism. It points out the reasons for female attraction to terrorism. It also shows the roles that women play in terrorist groups. The argument of this paper is that, instead of paradise, female jihadists, mostly those who left west countries, discover hell on earth. Besides, the paper proves article suggests that they represent a challenge and a threat after following the breakdown of the ISIS caliphate.